2011
DOI: 10.1371/journal.pone.0029026
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 and HIV-2 Infection Are Associated with Increased Mortality in a Rural West African Community

Abstract: BackgroundSurvival of people with HIV-2 and HTLV-1 infection is better than that of HIV-1 infected people, but long-term follow-up data are rare. We compared mortality rates of HIV-1, HIV-2, and HTLV-1 infected subjects with those of retrovirus-uninfected people in a rural community in Guinea-Bissau.MethodsIn 1990, 1997 and 2007, adult residents (aged ≥15 years) were interviewed, a blood sample was drawn and retroviral status was determined. An annual census was used to ascertain the vital status of all subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Finally, infection with both HIV-1 and HIV-2 generally carries the same prognosis and a similar mortality rate as HIV-1, except one study in rural community in Gambia which reported lower mortality among HIV-2-infected patients (van Tienen et al 2011). Two studies in Guinea-Bissau found conflicting results: (1) among 285 HIV-2-and 53 dual-infected patients, there found no difference in mortality with follow-up to 19 years in rural Caio (van Tienen et al 2011), and (2) among 223 patients that included 32 dually infected (14.3 %), it was suggested that being infected with HIV-1 and HIV-2 is associated to a slower rate of disease progression particularly in patients in whom HIV-2 infection preceded HIV-1 infection.…”
Section: Transmission and Disease Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, infection with both HIV-1 and HIV-2 generally carries the same prognosis and a similar mortality rate as HIV-1, except one study in rural community in Gambia which reported lower mortality among HIV-2-infected patients (van Tienen et al 2011). Two studies in Guinea-Bissau found conflicting results: (1) among 285 HIV-2-and 53 dual-infected patients, there found no difference in mortality with follow-up to 19 years in rural Caio (van Tienen et al 2011), and (2) among 223 patients that included 32 dually infected (14.3 %), it was suggested that being infected with HIV-1 and HIV-2 is associated to a slower rate of disease progression particularly in patients in whom HIV-2 infection preceded HIV-1 infection.…”
Section: Transmission and Disease Progressionmentioning
confidence: 99%
“…Two studies in Guinea-Bissau found conflicting results: (1) among 285 HIV-2-and 53 dual-infected patients, there found no difference in mortality with follow-up to 19 years in rural Caio (van Tienen et al 2011), and (2) among 223 patients that included 32 dually infected (14.3 %), it was suggested that being infected with HIV-1 and HIV-2 is associated to a slower rate of disease progression particularly in patients in whom HIV-2 infection preceded HIV-1 infection. These observations in a cohort with a long follow-up (approximately 20 years) showed that HIV-2 has an inhibitory effect of the rate of HIV-1 disease progression (Esbjornsson et al 2012).…”
Section: Transmission and Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest and most reliable estimates of mortality probably come from a study of deaths due to serologically confi rmed HIV-1, HIV-2, and HTLV-I infections among more than 5,000 residents of a rural area in northwestern Guinea-Bissau [ 50 ]. The study spanned the 18-year period before ART became available in 2007.…”
Section: Hiv-2mentioning
confidence: 99%
“…3 ), the most reliable mortality statistics probably come from Guinea-Bissau, where median survival with HIV-2 infection during the 18-year period before ART became available in 2007 was signifi cantly decreased compared with survival of uninfected individuals but approximately twice as long as in individuals with HIV-1 infection [ 50 ]. More on the reciprocal infl uences can be found in Sect.…”
Section: Mortalitymentioning
confidence: 99%